A Scoping Review on Staff Attitudes towards the Use of Coercion in Mental Healthcare - Efkemann, Simone Agnes; Lickiewicz, Jakub; Doedens, Paul; Lantta, Tella; Bali, Panagiota; Husum, Tonje Lossius (MDPI, 2025)
Attitudes of mental health professionals towards the use of coercion are highly relevant concerning its use coercion in mental healthcare, as mental health professionals have to weigh ethical arguments and decide within a legal frame in which situations to use coercion or not. Therefore, assessment of those attitudes is relevant for research in this field. A vital instrument to measure those attitudes towards the use of coercion is the Staff Attitude to Coercion Scale. This scoping review aims to provide a structured overview of the advantages and limitations in the assessment of attitudes toward coercion. We conducted a scoping review in Medline, PsycINFO, CINAHL, and Web of Science, based on the PRISMA-ScR. Inclusion criteria were empirical studies on the attitudes of mental health professionals. We included 80 studies and systematically mapped data about the main results and limitations in assessing attitudes toward coercion. The main results highlighted the relevance and increased interest in staff attitudes towards coercion in mental healthcare. Still, the majority of the included studies relied on a variety of different concepts and definitions concerning attitudes. The data further indicated difficulties in developing new and adapting existing assessment instruments because of the equivocal definitions of underlying concepts. To improve the research and knowledge in this area, future studies should be based on solid theoretical foundations. We identified the need for methodological changes and standardized procedures that take into account existing evidence from attitude research in social psychology, nursing science, and other relevant research fields. This would include an update of the Staff Attitude to Coercion Scale based on the limitations identified in this review.